Pengaruh Pemberian Jus Semangka Terhadap Status Hidrasi Pada Pekerja Sawit Bagian Perebusan Di Pt Tales Inti Sawit Desa Bandar Meria Bangun Purba - Wira Maria Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2021)
Hydration status can also be influenced by working environment conditions such as physical, chemical, biological, and psychological factors. The provision of watermelon juice is expected to maintain hydration status in employees who are exposed to heat and active physical activity. This study aims to find out how much influence the watermelon juice delivery has on the hydration status before and after giving watermelon juice in the PT.Tales Inti Sawit village of Bandar Meria Bangun Purba Village. This research is a quantitative research with a Quasi experimental approach with One Group Pretest and Postest Design. The population is 40 people. The sampling technique is using purposive sampling technique. in accordance with the criteria for a sample of 15 respondents. Hydration status was measured using Mission 7 Parameter Professional / GP Urinalysis Multisticks Urine. The mean hydration status of respondents before consumption of watermelon juice was 4.80 and the mean after giving watermelon juice was 5.47.The average work stress before and after consumption has increased This shows that watermelon juice affects the hydration status of workers which means there is a difference in the average work stress before consuming watermelon juice with after consumption of watermelon juice. Based on the Wilcoxon statistical test for hydration status before and after consumption of semanka juice shows a significance value of p = 0.004 (p≤0.05 means that consumption of watermelon juice affects the hydration status.Employees should consume watermelon juice instead of coffee consumption while working so as not to cause poor hydration status until they become dehydrated. the company should provide drinking water and provide watermelon juice to maintain the hydration status of special workers in the boiling section.